Sosialisasi Bahan Bulan Kitab Suci Nasional 2023 Dan Penyegaran Fasilitator Katekese Umat Di Paroki Santo Kristoforus Ba’a Rote - Yofince Abatan; Dorince Oetpah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
One of the national movements implemented by the Indonesian Catholic Bishops' Conference for Catholics throughout Indonesia is National Scripture Month which falls in September. During this month, Indonesian Catholics under the coordination of the Indonesian Biblical Institute held catechesis activities to encourage people to read and love the Word of God in the Holy Bible. In 2023, National Scripture Month will be held under the theme "God is the Source of Love and Salvation". So that all Catholics can understand the catechesis material for National Scripture Month, outreach is needed. In order for facilitators to be able to carry out the task of leading catechesis, catechesis refreshment is needed for facilitators. This is also needed by the Santo Kristoforus Ba'a Rote Parish. So, activities to disseminate materials for National Scripture Month and refresher catechesis are carried out as a form of service to the community. The methods used are lectures and discussions. The expected result is the congregation's understanding of the material for National Holy Bible Month 2023 and the facilitator's skills in leading the congregation's catechesis are refreshed.